Use of validation scales for hand and foot anesthesia simulators in teaching medical procedures (Research, Society and Development, 2022)
Objective: To demonstrate the process of elaboration and validation of Likert-type scales by Cronbach's alpha index, these scales are used to qualify the hand and foot truncal anesthesia training models through the perception of anesthesiology specialists. Method: Use of validation scales, based on the Likert pattern, for the approval of simulator models for teaching hand and foot anesthesia, from the application of questionnaires. Results and discussion: 70% of the sample were preceptors in medical residencies, all participants tested the models and filled out both questionnaires and answered “yes” or “no” to the question: “Is the questionnaire suitable for validating the evaluated model?”. The calculation of Cronbach's Alpha was performed on both scales, evaluating each item, whose result for both is between the range 0.7 – 0.9, giving very high reliability to the scales used. Conclusion: 90% of the specialists agree and approve the use of the scales, the Cronbach indices obtained excellent results, and the Likert-type scales validated the training model to aid in the teaching of medical sciences.